DEVELOPMENT OF AN ELECTRICAL SHRIMP TRAWL 1. REACTION OF SHRIMP TO LOW VOLT DIRECT CURRENT - NAMBOODIRI, K SREEDHARAN (Fishery Technology, 2025)
Preliminary attempts were made to assess the effect of direct current on shrimps and to see whether the shrimp could be guided in large numbers into the fishing net by using a current of appropriate voltage without scattering them away as it happens at present. This communication is the first in the series of studies and primarily deals with laboratory equipments and experimental procedures followed